2021
DOI: 10.1093/intimm/dxab075
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-17 family members in health and disease

Abstract: The interleukin-17 (IL-17) family consists of six family members (IL-17A–IL-17F) and all the corresponding receptors have been identified recently. This family is mainly involved in the host defense mechanisms against bacteria, fungi and helminth infection by inducing cytokines and chemokines, recruiting neutrophils, inducing anti-microbial proteins and modifying T-helper cell differentiation. IL-17A and some other family cytokines are also involved in the development of psoriasis, psoriatic arthritis and anky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 69 publications
(108 reference statements)
1
62
0
Order By: Relevance
“…Previous studies showed that Th1, Th2, Th9, and Th17 immune responses play important roles in fighting parasitic infections ( 47 – 50 ). Our results showed that rHc-TPS co-incubation with PBMCs significantly inhibited the transcriptional levels of IFN-γ, IL-4, and IL-9, which may exert one of the pathways of immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that Th1, Th2, Th9, and Th17 immune responses play important roles in fighting parasitic infections ( 47 – 50 ). Our results showed that rHc-TPS co-incubation with PBMCs significantly inhibited the transcriptional levels of IFN-γ, IL-4, and IL-9, which may exert one of the pathways of immune evasion.…”
Section: Discussionmentioning
confidence: 99%
“…The Th17 cell has been studied intensively in autoimmune diseases due to its capacity to induce inflammation. Its signature cytokines, including IL-17A and IL-17F, promote the production of proinflammatory molecules from various immune and non-immune cells, and recruit inflammatory cells—such as neutrophils and macrophages—to the inflammatory site [ 35 ]. Recent studies revealed that Th17 cells also express IL-24.…”
Section: Immunobiology Of Il-24mentioning
confidence: 99%
“…IL-17 affects tissue cells and IL-17 receptors are expressed in all epithelial cells. 12 IL-17 has related allergic responses and is elevated mainly in acute and severe forms of allergic diseases. 10 12 The IL-17 family consists of 6 members (IL17A to IL-17F).…”
mentioning
confidence: 99%
“… 12 IL-17 has related allergic responses and is elevated mainly in acute and severe forms of allergic diseases. 10 12 The IL-17 family consists of 6 members (IL17A to IL-17F). The IL-17 receptors, IL-17RA, IL-17RB/IL-25R, IL-17RC, IL-17RD/SEF, and IL-17RE, play a role in the development and exacerbation of allergic diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation